Case Report: Diagnosis of Gaucher disease in a toddler with acute respiratory failure - Householder, Sarah; Nagar, Ruchit; Shah, Nisarg; Forward, Jodi; Bickerton, Sean; Mistry, Pramod; Faustino, E. Vincent S. (Frontiers in Pediatrics, 2025)
A 22-month-old male infant presented with cyanosis and stridor after a trivial fall and then developed acute respiratory distress. The respiratory status of the patient progressed rapidly to severe acute respiratory distress syndrome. Additional findings of hypersplenism prompted a comprehensive multidisciplinary approach and consideration of an inborn error of metabolism. Rapid whole genome sequence showed a compound heterozygote mutation in the GBA1 gene involving a maternally inherited known pathogenic variant, p.L483P, and a paternally inherited novel likely pathogenic variant, p.P358l. The diagnosis of Gaucher disease was confirmed with low leukocyte acid β-glucosidase activity and the patient received recombinant macrophage-targeted enzyme replacement therapy. The patient eventually recovered, but subsequent work-up demonstrated severe bulbar dysfunction with evidence of aspiration. Two months after discharge, the patient arrived at the hospital in a condition of cardiac arrest after a suspected aspiration event associated with hemoptysis. This case illustrates a previously undescribed presentation of Gaucher disease and a new likely pathogenic genetic variant for Gaucher disease. It highlights the role of a multidisciplinary approach, including rapid whole-genome sequencing, to establish timely diagnosis and provide appropriate therapy for Gaucher disease.